HUBUNGAN KETEPATAN PENGELUARAN PEMERINTAH DAERAH BERDASARKAN FUNGSI ANGGARAN TERHADAP KESEJAHTERAAN MASYARAKAT DAERAH TERTINGGAL - Siswantoro, Siswantoro (Badan Perencanaan Pembangunan Penelitian dan Pengembangan Daerah Kabupaten Cilacap, 2023)
One of the main problems in underdeveloped areas is the low level of social welfare. To overcome this problem, the government allocates expenditure funds as a funding instrument to improve people's welfare. The aim of the study was to determine the relationship between the accuracy of government budget spending by function in 122 underdeveloped regions in Indonesia with using the three indicators of the human development index (IPM) (indicators of health, education, and economy) as benchmarks for assessing people's welfare. According to previous studies, the variables of poverty and population growth are also included in this study as control variables. This research method is a multiple linear analysis with the selected model, namely the fixed effect model. The data used is panel data which consists of 122 data in underdeveloped areas over a period of 4 years. The results showed that the probability value of local government spending according to the economic function was 0.0473 bigger 5% with a regression coefficient of 0.003102. The results of these statistics conclude that there is a correlation between the accuracy of the economic function of regional government budget spending which is significant for the welfare of disadvantaged areas.